The four pillars of investing : lessons for building a winning portfolio - Bernstein, William J. (McGraw Hill-Ascent Audio, 2010)
The classic guide to constructing a solid portfolio-without a financial advisor! "With relatively little effort, you can design and assemble an investment portfolio that, because of its wide diversification and minimal expenses, will prove superior to the most professionally managed accounts. Great intelligence and good luck are not required." William Bernstein's commonsense approach to portfolio construction has served investors well during the past turbulent decade-and it's what made The Four Pillars of Investing an instant classic when it was first published nearly a decade ago. This down-to-earth book lays out in easy-to-understand prose the four essential topics that every investor must master: the relationship of risk and reward, the history of the market, the psychology of the investor and the market, and the folly of taking financial advice from investment salespeople. Bernstein pulls back the curtain to reveal what really goes on in today's financial industry as he outlines a simple program for building wealth while controlling risk. Straightforward in its presentation and generous in its real-life examples, The Four Pillars of Investing presents a no-nonsense discussion of: The art and science of mixing different asset classes into an effective blend The dangers of actively picking stocks, as opposed to investing in the whole market Behavioral finance and how state of mind can adversely affect decision making Reasons the mutual fund and brokerage industries, rather than your partners, are often your most direct competitors Strategies for managing all of your assets-savings, 401(k)s, home equity-as one portfolio Investing is not a destination. It is a journey, and along the way are stockbrokers, journalists, and mutual fund companies whose interests are diametrically opposed to yours. More relevant today than ever, The Four Pillars of Investing shows you how to determine your own financial direction and assemble an investment program with the sole goal of building long-term wealth for you and your family